Folliculotropic mycosis fungoides: Clinical characteristics, treatments, and long‐term outcomes of 53 patients in a tertiary hospital. Issue 4 (1st June 2020) - Kalay Yildizhan, Incilay; Sanli, Hatice; Akay, Bengu N.; Uzundere, Ceren; Okcu Heper, Aylin
Abstract: Folliculotropic mycosis fungoides (FMF) is characterized by a broad clinical spectrum and worse prognosis compared to classical MF. This study aimed to evaluate the clinical characteristics, treatment modalities and long‐term outcome and risk factors for progression and survival of FMF patients. We conducted a single‐center retrospective study and reviewed 53 patients diagnosed with FMF between 1990 to 2019 in a referral center at Ankara University, Turkey. Regarding to stage at diagnosis, 24 patients (45.3%) had advanced‐stage disease (≥IIB). Follicular papules was observed in 66% and alopecia in 49.1% of the cases. Forty‐three patients (81.1%) suffered from pruritus. The majority of the patients (92.4%) had at least one systemic therapy. Complete remission was achieved in 24.5% of the patients. The median time of overall survival (OS) was 50 months (range 9‐324 months) and 5‐year and 10‐year OS was 83% and 69%, respectively. Twenty‐eight (52.3%) patients progressed to more advanced stages and seven (13.2%) patients died due to MF during the follow‐up period. FMF is associated with a progressive course and in most patients, skin‐directed therapies were found to be inefficient to control the disease and multiple systemic therapeutic agents were required to control the disease.